Correlation Between Learning Outcomes and Spiritual Attitudes Through the Implementation of Chemistry Teaching Materials Based on Spiritual Value Using the Process-Oriented Guided Inquiry Learning (POGIL) Model on Hydrocarbon Topics for Class XI - Juwita, Intan; Khairunisa, Dira; Br Tarigan, Ayu Mutia; Zain, Zeilla Ramadhani; Hasibuan, Anisya Humaida; Siregar, Arliani Panaulan; Darmana, Ayi (Jurnal Pendidikan dan Pembelajaran Kimia, 2024)
The purpose of this study was to determine the relationship between learning outcomes and students' spiritual attitudes through the implementation of spiritual value-based chemistry teaching materials with the POGIL model on Hydrocarbon material in class XI Matlanfor SMA Negeri 1 Percut Sei Tuan. This type of research is correlational research. The data collected were in the form of learning outcome test instruments and non-test spiritual attitude questionnaires. The results of the study were that there was a significant positive relationship between students' spiritual attitudes and increased learning outcomes after using integrated chemistry teaching materials with spiritual values in class XI Matlanfor with a Sig. (2-tailed) value of 0.003 ≤ α (0.05) obtained a person correlation value of 0.243 indicating that students' spiritual attitudes contributed 24.3% to the learning outcomes of class XI Matlanfor students of SMA Negeri 1 Percut Sei Tuan.Keywords: Learning Outcomes, Spiritual Atttudes, POGIL, Spiritual ValueDOI: 10.23960/jppk.v13.i3.32145